‘Close as a kiss’: Gyn/Affection in Margaret Atwood’s The Penelopiad - Rodríguez Salas, Gerardo (Amaltea. Revista de Mitocrítica, 2015)
Margaret Atwood’s novella The Penelopiad (2005) seemingly celebrates Penelope’s agency in opposition to Homer’s myth in The Odyssey. However, the twelve murdered maids steal the book to suggest the possibility of what Janice Raymond calls gyn/affection, a female bonding based on the logic of emotion that, in Atwood’s revision, verges on Kristevan abjection, the sinister and the fantastic, and serves a cathartic effect not only in the maids but also in the reader. This essay aims to question the generally accepted empowerment of Atwood’s Penelope and celebrates the murdered maids as the locus of emotion, where marginal aspects of gender and class merge to weave a powerful metaphorical tapestry of popular and traditionally feminized literary genres that, in plunging into and embracing the semiotic realm, ultimately solidify into an eclectic but compact alternative tradition of women’s writing and myth-making.